Why They Went to Russia - Jorge M. Reverte (Cuadernos de Historia Contemporánea, 2012)
This article outlines the positions of the army and the Falange in creating a corp of volunteers for taking part in the German Invasion of the USSR. The autor describes the volunteers experiences.